Clean Water For Small Islands In Indonesia: Case Study Of Child Diarrhea In Kelapa And Kelapa Dua Islands, Kepulauan Seribu - Mukharomah, Nur Ariati; Achmadi, Umar Fahmi (Poltekkes Kemenkes Semarang, 2024)
Clean water quality/water sources are critical factors in preventing diarrhea, especially in island areas that often face challenges of limited access and infrastructure to provide adequate clean water. This study aimed to see the descriptive relationship between the physical and microbiological quality of dug well water and the incidence of diarrhea in children on Kelapa Island and Kelapa Dua Island, Kepulauan Seribu. The results of the analysis showed that the physical quality of water in both locations met the criteria of the Minister of Health Regulation number 2 of 2023, namely, the temperature was in the range of 24Â°C-30Â°C, turbidity <1 NTU, and water that was odorless and colorless. Microbiological analysis revealed significant contamination, with total Coliform Bacteria and Escherichia coli levels exceeding the maximum allowable limit (> 0 CFU/100 ml ). Factors such as shallow well depths of less than 3 meters and well distances of less than 10 meters from pollution sources contribute to water pollution indicates fecal contamination that increases the risk of diarrhea, especially in children under five. Given the island region's limited access to water quality, these findings emphasize the need for improved water quality monitoring and environmental quality improvements to reduce public health impacts.